Rituals of Islamic spirituality : a study of Majlis Dhikr groups in East Java - Zamhari, Arif (Islam in Southeast Asia series (Canberra (A.C.T.)), 2010)
"This study examines the emergence of new forms of Islamic spirituality in Indonesia identified as Majlis Dhikr. These Majlis Dhikr groups have proliferated on Java in the last two decades, both in urban and rural areas, and have attracted followers from a wide social background. The diverse aspects of these Majlis Dhikr groups - their rituals, teachings and strategies of dissemination as well as the popular understanding of these rituals and their contestation by critics and opponents - are examined in detail and illustrated by reference to three particular groups - Salawat Wahidiyat, Istighathat Ihsaniyyat and Dhikr al-Ghafilin each of which has its own distinctive features and notable religious leadership. These Majlis Dhikr groups regard their activities as legitimate ritual practices that are in accordance with the legacy of Islamic Sufism based on the interpretation of the Qur'anic and Prophetic tradition."--Publisher's description